Adsorption of anionic and cationic dyes by a novel crosslinked cellulose-tetrafluoroterephthalonitrile-tannin polymer. (5th November 2022) - Lv, Hu-Wei; Jiang, Hong-Liu; He, Fu-An; Hu, Qing-Di; Zhong, Zhu-Rui; Yang, Yong-Yu
Graphical abstract: Highlights: A novel crosslinked CETTA was synthesized by a one-step reaction for dye adsorption. CETTA possessed high adsorption capacities for both cationic MB and anionic XO dyes. CETTA exhibited good reused ability for both cationic MB and anionic XO dyes. Abstract: A novel crosslinked cellulose-tetrafluoroterephthalonitrile-tannin (CETTA) polymer with the excellent adsorption performance for both cationic and anionic dyes was synthesized by a one-step reaction, and its structure was investigated by SEM, FTIR, TGA, XPS, and zeta potential measurement. It was found that the adsorption ability of the CETTA changed with the pH value of the dye solution because the electrostatic interaction played an important role in the dye adsorption process. The maximum adsorption capacities of the CETTA at 303 K for the cationic methylene blue (MB) and the anionic xylenol orange (XO) dye reached as high as 953 mg/g at pH = 10 and 232 mg/g at pH = 1, respectively. The adsorption behaviors of the CETTA for both the MB and the XO were not only spontaneous but also in accordance with the pseudo-secondary adsorption kinetic model and the linear Langmuir adsorption isotherm model. Additionally, the CETTA possessed the good reused ability for the dye adsorption.